2020
DOI: 10.1186/s12864-020-06910-6
|View full text |Cite
|
Sign up to set email alerts
|

Completion of draft bacterial genomes by long-read sequencing of synthetic genomic pools

Abstract: Background: Illumina technology currently dominates bacterial genomics due to its high read accuracy and low sequencing cost. However, the incompleteness of draft genomes generated by Illumina reads limits their application in comprehensive genomics analyses. Alternatively, hybrid assembly using both Illumina short reads and long reads generated by single molecule sequencing technologies can enable assembly of complete bacterial genomes, yet the high per-genome cost of long-read sequencing limits the widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…DNA was extracted from these isolates using the Qiagen DNeasy blood and tissue kit (Qiagen, Hilden, Germany), according to the manufacturer’s instructions, and normalized to 5 ng/μl using the Qubit dsDNA (double-stranded DNA) HS kit (Life Technologies, Carlsbad, CA, USA). Sequencing and draft genome assembly were conducted as described previously by Derakhshani et al ( 40 ) for barcoded Illumina HiSeq reads. Briefly, sequencing libraries were prepared using the NEBNext Ultra II FS DNA library prep kit for Illumina (New England BioLabs [NEB], Ipswich, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from these isolates using the Qiagen DNeasy blood and tissue kit (Qiagen, Hilden, Germany), according to the manufacturer’s instructions, and normalized to 5 ng/μl using the Qubit dsDNA (double-stranded DNA) HS kit (Life Technologies, Carlsbad, CA, USA). Sequencing and draft genome assembly were conducted as described previously by Derakhshani et al ( 40 ) for barcoded Illumina HiSeq reads. Briefly, sequencing libraries were prepared using the NEBNext Ultra II FS DNA library prep kit for Illumina (New England BioLabs [NEB], Ipswich, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A more recent study showed that the use of long-read technologies (e.g., PacBio) improved drastically the completeness of the MAGs and associated predicted genes: more than 98% of the genes predicted from PacBio-assembled MAGs were complete compared to only 40% using HiSeq-assembled MAGs ( Xie et al, 2020 ). Indeed, the use of long reads enables the detection of repeated elements often found in ribosomal RNA genes or bacteriophage-related insertions that are frequently missed with short read sequencing ( Derakhshani et al, 2020 ).…”
Section: Final Considerationsmentioning
confidence: 99%
“…As the study was based on draft genome sequences, it is challenging to study repetitive elements like insertion sequence (IS) elements and other mobile elements such as plasmids integrons, CRISPRs, conjugative transposons, and phages. With the advent of third-generation sequencing, it is possible to obtain complete genome sequences to understand intragenomic heterogeneity and inter-strain variations in an effective manner [14]. In the present study, we provide evidence for genome expansion and the role of specific IS elements along with plasmids in the ecological diversification of S. haemolyticus.…”
Section: Introductionmentioning
confidence: 69%